2010
DOI: 10.1177/1744629510386289
|View full text |Cite
|
Sign up to set email alerts
|

Exploring decision making in intellectual disability nursing practice: a qualitative study

Abstract: Due to the dearth of relevant research, intellectual disability nurses may have difficulty identifying sources of evidence on which they can base their clinical decisions. The aim of the present research was to explore how intellectual disability nurses make decisions and how their decisions are influenced by evidence. The method was guided by interpretative phenomenology and the analysis adopted an idiographic approach. Twelve National Health Service intellectual disability nurses in Wales participated in sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
(76 reference statements)
0
8
0
1
Order By: Relevance
“…This is in line with the findings of Williams et al . (), who found that listening to the person with ID is central to the decision‐making of ID nurses. Nonetheless, only 8% of the care staff and ID physicians explicitly mentioned that the wishes or preferences of the client were taken into account in actual decisions, while the wishes and preferences of family members were mentioned twice as often (15%).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of Williams et al . (), who found that listening to the person with ID is central to the decision‐making of ID nurses. Nonetheless, only 8% of the care staff and ID physicians explicitly mentioned that the wishes or preferences of the client were taken into account in actual decisions, while the wishes and preferences of family members were mentioned twice as often (15%).…”
Section: Discussionmentioning
confidence: 99%
“…It can also mean providing physical care such as oral and personal hygiene, attending to matters of sexual health, and conducting mobility assessment (McKeon, ; Nelson & Carey, ; Taggart, Truesdale‐Kennedy, & McIlfatrick, ). Finally, it can mean delivering relational or psychological care such as client advocacy, assistance with decision making, behavioural management and counselling (Llewellyn & Northway, ; Sheerin & McConkey, ; Williams, Roberts, Irvine, & Hastings, ).…”
Section: Resultsmentioning
confidence: 99%
“…Some nurses have expressed a need for training and education in advocacy to support the health and well‐being of their clients (Llewellyn & Northway, ). Others have suggested that education founded on appropriate research would greatly enhance the decision‐making processes of nurses working with people with ID through influencing person‐centred thinking and better using evidence from the person with ID (Williams et al., ). Additionally, client education and health promotion has been described as a key role for nurses working with people with ID (O'Connor & Carey, ; Taggart et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the patient and team working constituted key factors in making decisions, concurring with Williams et al . (), although there was sparse reference to recognized sources of evidence, an acknowledged problem in learning disability nursing (Girot ) because of the limited research base (Griffiths et al . ).…”
Section: Discussionmentioning
confidence: 99%